Marfan Syndrome and Autosomal Dominant Polycystic Kidney Disease: A Case of Rare Co-occurrence or Coincidence? - Arjun Sekar (European Medical Journal)
Background: Marfan syndrome (MFS) and autosomal dominant kidney disease (ADPKD) are two separate genetic disorders. The author describes the case of a young male with ADPKD who incidentally had Marfan-like features. A literature review was carried out to see if these two disorders could be linked. Case presentation: A young male presented for incidentally found renal cysts. Kidney function was well preserved, but the patient had positive family history of ADPKD. During routine follow-up, a history of aortic valve disease was mentioned. This, along with the patient’s tall, lean stature and long extremities raised the concern for MFS. A detailed physical examination and workup by other specialists confirmed a clinical diagnosis of MFS. They had no known family history of MFS. The patient has been followed at Associates in Kidney Care, Des Moines, Iowa, USA, for the past 2 years. Discussion: There are several reports of overlap of ADPKD and connective tissue disorders with an overlap of vascular disorders. ADPKD and MFS are caused by totally different mutations. However, the literature review showed that vascular abnormalities and connective tissue diseases may be more common with ADPKD. Studies have shown that there could be a common signalling pathway for connective tissue disorders when both genes are affected simultaneously. Further research is needed to identify these pathways. More frequent screening of vascular abnormalities might be warranted in those with both phenotypes.